(untitled) (Tribhuvan University Journal of Microbiology, 2025)
Objectives: To assess the quality of drinking water microbiologically as well as to monitor various physicochemical quality parameters. Methods: The study was a laboratory-based cross-sectional study. Thirty samples of water were taken without contamination from different sources such as stone spouts, boring wells, pumps, dug wells, tap water and jar water. The samples were transported with a cold chain maintained and analyzed promptly. Physicochemical parameters were identified using methods indicated in APHA (2005). Spread plate technique and membrane filtration technique were conducted for total bacterial load count and total coliform load count respectively. Bacterial pathogens were isolated and identified through selective enrichment and culture on specific media as well as using biochemical characterstics. Kirby-Bauer disk diffusion technique was used to determine the antibiotic susceptibility pattern of the isolates which revealed varying rates of resistance among the isolates with some of them having multi-drug resistance. Results: The findings indicated that the highest bacteria loads were on pump (1.43 ×106 cfu/ml) and stone spout water (1.02 ×106cfu/ml), whereas, jar water was not contaminated. In stone spout water counts of coliform were recorded at (70 cfu /ml). Conclusion: The most frequently isolated pathogens were E. coli and Klebsiella spp. Isolates showed resistance to amoxicillin which could mean there are threats to health and therefore better monitoring and treatments of water quality should be considered.